Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities, 2021)
This issue of KIU Journal of Humanities touches on Development Administration and Social Psychology. The first part of the Journal addresses issues in Development Administration such as Local Government Administration, Religious Politics, Police Reforms and Costitutional Design. Using Nigerian Police Service Reform as a Case Study, one of the papers in this section argues, among other things, that the poor performance of Nigeria Police is more of an orientational, than structural, problem.  It, therefore, concludes that the right change in the orientation and approach of the police, the government, and other stakeholders to police reforms will make the police function expectedly.  So, it is recommended that the process of change of orientation, approach, and, maybe, structure of the police should be designed to be a collective effort of all the stakeholders. The second section which centers on Social Psychology, examines various psychology factors which have impacts on the society, and these include sexual education, psychopathy among criminals and non criminals, use of social media and organizational reward system. One of these papers reveals that among others that teachers and parents have a good attitude about sexuality education as a subject in Nigerian secondary schools. Based on the findings, the paper recommends that sexuality education should be introduced in schools early enough. Since both parents and teachers are understandably disposed to sexuality education, public enlightenment should be carried out to improve on public attitude towards sexuality education. In all, this issue of KIU Journal of Humanities features many empirical and theoretical based articles which can be of great benefit to every reader.